Sosialisasi Hidup Sehat dan Senam Aerobik Pada Siswa SMA Negeri 2 Kabanjahe Kabupaten Karo - Sitepu, Deasyi Natalia; Tamba, Tri Widia Astuti; Sinurat, Hasiholanta; Josua; Rafael Mey Hagata Sembiring (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
Students' health problems can worsen due to lack of exercise, causing the body to become stressed and appear unfit. Exercise, both directly and indirectly, is very beneficial for overall health. Exercise is also a physical activity that can be used as part of a healthy lifestyle to improve body health and support several daily tasks. However, many people still underestimate the need to exercise every day to maintain physical and mental health. Thus, based on this scenario, individuals really need information about healthy living through sports and health education in order to meet healthy and healthy living standards. The aim of holding sports and health education at SMA Negeri 2 Kabanjahe through community service is to provide information and knowledge to the public about healthy lifestyles through sports and public health education which can provide benefits for the body. The results of this service show that students are very enthusiastic about participating in the event from start to finish.